82.4k views
2 votes
Which expression is equivalent to the given expression? Assume the denominator does not equal zero. Please give a detailed explanation and not just the answer; explain the concept to me, step by step what to do to solve this problem. Thank you.

Which expression is equivalent to the given expression? Assume the denominator does-example-1

1 Answer

4 votes

Solution

- The solution steps are given below:


\begin{gathered} ((4m^5n^2)/(m^2n))^3 \\ \\ =((4* m^(2+3)n^(1+1))/(m^2n))^3 \\ \\ =((4* m^2n* m^3n)/(m^2n))^3 \\ \\ =((4* m^3n)/(1))^3 \\ \\ =4^(1*3)* m^(3*3)* n^(1*3) \\ \\ =4^3m^9n^3 \\ \\ =64m^9n^3\text{ \lparen OPTION A\rparen} \end{gathered}

User Sandric
by
5.3k points